Implementasi Standar Audit 500 pada Prosedur Audit Kas Oleh KAP X: Studi Kasus pada BLUD - Leksono, Bagus Budi Bowo; Widoretno, Astrini Aning (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
This study aims to evaluate the appropriateness of the audit procedures for the cash account conducted by Public Accounting Firm (KAP) X at a Regional Public Service Agency (BLUD) with the provisions stipulated in Auditing Standard (SA) 500 concerning audit evidence. This research employed a qualitative descriptive method. Data were obtained through direct observation and documentation of various audit evidence, such as cash reconciliation results, official reports of physical cash counts (cash opname), and bank balance confirmations. The results of the study indicate that the audit procedures implemented by KAP X are in accordance with the provisions of SA 500. This is reflected in the execution of procedures such as the verification of cash balances, periodic physical examinations, the application of analytical procedures, external (third-party) confirmations, evaluation of cash account transactions, and the disclosure of cash information in the financial statements. All these steps support the acquisition of sufficient and reliable audit evidence. Therefore, the audit has contributed to strengthening the accountability of cash management within the BLUD environment. In conclusion, the cash audit practices conducted by KAP X comply with the principles regulated in SA 500 and can serve as a reference for enhancing the quality of audits in the public sector.